Cryptanalysis using biological inspired computing approaches - Ahmad, Badrisham; Maarof, Mohd. Aizaini (2006)

(untitled)
In security, cryptology is introduced to guarantee the safety of data, whereby it is divided into cryptography and cryptanalysis. Cryptography is a technique to conceal information by means of encryption and decryption while cryptanalysis is used to break the encrypted information using some methods. Biological Inspired Computing (BIC) is a method that takes ideas from biology to be used in computing. BIC is a field that has been widely used in many computer applications such as pattern recognition, computer and network security and optimization. Some examples of BIC approaches are genetic algorithm (GA), ant colony and artificial immune system (AIS). GA and ant colony have been successfully applied in cryptanalysis of classical ciphers. Therefore, this paper will review these techniques and explore the potential of using AIS in cryptanalysis.